Relationship of black layer and milk line development on maize seed maturity - Vieira, Roberval Daiton [UNESP]; Minohara, L. [UNESP]; Carvalho, N.M. de [UNESP]; Bergamaschi, M.C.M. [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 1995)
A relação entre o desenvolvimento da camada negra e da linha de transformação em amido e a maturidade fisiológica de sementes de milho foi estudada durante dois anos agrícolas (1990/91 e 1991/92). Para atingir os objetivos do trabalho, avaliou-se o grau de umidade, a germinação, o vigor (envelhecimento acelerado, teste frio e condutividade elétrica) e o desenvolvimento da camada negra e da linha de transformação em amido para dois genótipos (CX 133 e IAC 100). Com base nos resultados de germinação e vigor das sementes verificou-se que a maturidade fisiológica foi alcançada antes do estádio 4. Por outro lado, graus de umidade de 30 a 35% foram alcançados somente no estádio de desenvolvimento 4. A linha de transformação em amido provou ser um instrumento útil para predizer a maturidade fisiológica e de colheita para sementes de milho.

The relationship of black layer and milk line development on maize seed maturity was evaluated under tropical conditions. Seed moisture (g.kg-1), standard germination - SG (7 days, 25°C), and vigor, using accelerated aging-AA (96 hours, 42°C and 100% of RH), cold test-CT only in 1991/92 (7 days at 10°C and 7 days at 25°C) and electrical conductivity-EC (four 50-seed samples, 24 hours imbibition at 25°C) and milk line and black layer formation (using a five-stage rating system) were determined at 3 to 4 days intervals, using two genotypes (hybrid CX 133 and variety IAC 100) during the crop seasons of 1990/91 and 1991/92. The results showed that physiological maturity was reached before stage 4, based on seed germination and vigor (AA and CT) values, which occurred before that stage and presented the lowest values of EC. on the other hand, moisture content levels of 300 to 350 g.kg-1 were reached only at stage 4. The milk line ratings proved useful in predicting physiological maturity as well as the harvest maturity.
Relação entre o desenvolvimento da camada negra e da linha de transformação em amido e a maturidade de sementes de milho
Keywords: Germination; Vigor; accelerated aging; cold test; Electrical conductivity; Germinação; Vigor; envelhecimento acelerado; Condutividade elétrica; teste frio